Predictive factors of cytomegalovirus seropositivity among pregnant women in Paris, France. - Dieynaba S N'Diaye; Yazdan Yazdanpanah; Anne Krivine; Thibaut Andrieu; Flore Rozenberg; Olivier Picone; Vassilis Tsatsaris; François Goffinet; Odile Launay (PLoS ONE)
Background Cytomegalovirus (CMV) is the most frequent cause of congenital infection. The objective of this study was to evaluate predictive factors for CMV seronegativity in a cohort of pregnant women in Paris, France. Methods Pregnant women enrolled in a prospective cohort during the 2009 A/H1N1 pandemic were tested for CMV IgG antibodies. Variables collected were age, geographic origin, lifestyle, work characteristics, socioeconomic status, gravidity, parity and number of children at home. A multivariate logistic regression model was used to identify independent predictive factors for CMV seropositivity. Results Among the 826 women enrolled, 389 (47.1%) were primiparous, and 552 (67.1%) had Metropolitan France as a geographic origin. Out of these, 355 (i.e. 57.0%, 95% confidence interval (CI): [53.6%-60.4%]) were CMV seropositive: 43.7% (95% CI:[39.5%-47.9%]) in those whose geographic origin was Metropolitan France and 84.1% in those with other origins (95% CI:[79.2%-88.3%]). Determinants associated with CMV seropositivity in a multivariate logistic regression model were: (i) geographic origin (p<0.001(compared with Metropolitan France, geographic origins of Africa adjusted odds ratio (aOR) 21.2, 95% CI:[9.7-46.5], French overseas departments and territories and other origin, aOR 7.5, 95% CI:[3.9-14.6], and Europe or Asia, aOR 2.2, 95% CI: [1.3-3.7]); and (ii) gravidity (p = 0.019), (compared with gravidity = 1, if gravidity≥3, aOR = 1.5, 95% CI: [1.1-2.2]; if gravidity = 2, aOR = 1.0, 95% CI: [0.7-1.4]). Work characteristics and socioeconomic status were not independently associated with CMV seropositivity. Conclusions In this cohort of pregnant women, a geographic origin of Metropolitan France and a low gravidity were predictive factors for CMV low seropositivity. Such women are therefore the likely target population for prevention of CMV infection during pregnancy in France.